Environmental impacts of using recycled plastics in concrete - Furqan Tahir (14429547) (2022)
The urbanization process adds to the increase in solid waste generation, increased environmental impacts, and solid waste management failures. Due to the restricted deployment and proper disposal of solid waste, the environmental implications are a concern. There has been an increase in interest in sustainable practices regarding waste management and recycling, which the civil construction sector has substantially absorbed. Plastic waste can be recycled and can be used in many applications. One such application is in concrete, for which the recycled-based plastic aggregates or plastic fibers can be substituted for natural aggregates or steel-reinforced mesh (SRM). Many researchers have investigated the mechanical properties of such concrete; however, the environmental assessments are limited in the literature. This research evaluates and consolidates environmental studies on recycled plastics in concrete-like aggregates and fibers. A summary of the applications of recovered plastics is presented. Following that, the works on environmental implications are thoroughly discussed and analyzed. In addition, research gaps and challenges related to environmental assessments are highlighted in this work. Other Information Published in: Materials Today: Proceedings License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.matpr.2022.04.593